Implementing psychosocial guidelines into specialized spinal cord injury rehabilitation services to strengthen person-centred health care: protocol for a mixed methods study - Candice McBain; Candice McBain; Anne Marie Sarandrea; Anne Marie Sarandrea; Anne Marie Sarandrea; Ilaria Pozzato; Ilaria Pozzato; Mohit Arora; Mohit Arora; Daniel Myles; Daniel Myles; John Bourke; et al. (Frontiers in Rehabilitation Sciences)
BackgroundSpinal cord injury (SCI) is a severe neurological disorder resulting in loss of movement and altered sensation with lifelong impacts on health, function, and social integration. Multidisciplinary SCI rehabilitation primarily focuses on enhancing function and independence while simultaneously managing secondary health conditions and providing psychosocial support. Therefore, a major goal in SCI rehabilitation should be strengthening patients’ capacity to cope with and adjust to challenges they encounter. Using a mixed methods design, the primary aim of this study is to integrate psychosocial guidelines that promote psychological adjustment into SCI rehabilitation, and second, to evaluate facilitators and barriers to their successful implementation.MethodsTo determine perceived depth of knowledge, beliefs, and attitudes about psychosocial care, and usage of psychosocial guidelines, healthcare professionals in the three specialist SCI services in New South Wales, Australia will be invited to complete a baseline survey. Following the survey, semi-structured one-to-one interviews and focus groups will be conducted with healthcare professionals representing different health disciplines to understand the context and generate ideas about how best to integrate these guidelines into clinical practice. Based on the surveys, interviews, and focus groups, an implementation intervention employing educational strategies, structural, and nudge (behavioural change) approaches will be designed and implemented over a period of 18-months to facilitate integration of the guidelines into the SCI services. A post-intervention survey with healthcare workers will then be conducted. Focus groups from each SCI service, with representation across the different healthcare professions, will also be conducted to identify facilitators and barriers to implementing the guidelines. Success of implementation will be determined by analyzing any shifts in perceived knowledge, attitudes, and behaviour of staff and cultural/structural processes observed through comparing baseline and post-intervention qualitative and quantitative data. To capture lived experience insight, 10 patients with SCI currently undergoing rehabilitation will be interviewed.DiscussionThis study will establish the success of implementing psychosocial guidelines into three specialist SCI services. It is hypothesized that constructive changes will occur in the knowledge, attitudes, and behaviour of the SCI Unit healthcare professionals, leading to improved psychosocial practices and patient outcomes that will strengthen person-centred healthcare in SCI rehabilitation. This study has been retrospectively registered with the Australian New Zealand Clinical Trials Registry on the 7th of May 2024. The registration number is: ACTRN12624000581561